Analysis of Internal Control, Good Corporate Governance and Reporting System Against Fraud - Ade Onny Siagian; Adler Haymans Manurung; Tri Widyastuti; Zahara Tussoleha Rony (International Journal of Management Research and Economics, 2023)
The aim of this research is that fraud is still rampant in Islamic banks, both internal and external, to obtain empirical evidence regarding the influence of internal control, good corporate governance and Violation reporting system on fraud in Islamic banks registered with the Financial Services Authority (OJK) for the 2020-2022 period. This research is quantitative in nature using secondary data in the form of annual reports of sharia banking companies for 2020-2022. The samples taken using purposive sampling were 14 companies. Data analysis uses multiple linear regression analysis with SPSS version 26 software. The research results show that the good corporate governance variable has an effect on fraud. However, the internal control variable has no effect on fraud and the Violation reporting system variable has no effect on fraud. Good corporate governance, internal control, and a violation reporting system simultaneously influence fraud. The results of this research have implications for sharia banking management to further strengthen the implementation of GCG to reduce the level of fraud in sharia banking.